2001
DOI: 10.1124/mol.60.5.1049
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H2 Receptor Desensitization: Involvement of a Select Array of G Protein-Coupled Receptor Kinases

Abstract: The histamine H2 receptor (H2r) belongs to the heptahelical receptor family; upon agonist binding, members of this family activate a G protein and the downstream effector adenylyl cyclase. Like other G protein-coupled receptors, exposure of H2r to agonists produces a desensitization of the response. The present study focused on the desensitization mechanism of this receptor. Using transiently transfected COS-7 cells expressing tagged-H2r, the desensitization induced by amthamine, characterized by decreased cAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…We have reported previously that H2r exposure to amthamine induces a rapid and homologous desensitization (Lemos Legnazzi et al, 2000;Shayo et al, 2001). In the present study, we found that H2r internalized after agonist exposure and that the loss of cAMP response was observed earlier than that of H2r membrane sites (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We have reported previously that H2r exposure to amthamine induces a rapid and homologous desensitization (Lemos Legnazzi et al, 2000;Shayo et al, 2001). In the present study, we found that H2r internalized after agonist exposure and that the loss of cAMP response was observed earlier than that of H2r membrane sites (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…We reported previously that a rapid homologous desensitization of the H2r is observed in transfected COS7 cells and U937 cells (Lemos Legnazzi et al, 2000;Shayo et al, 2001). In addition, Smit and coworkers (1995) showed the loss of H2r membrane immunofluorescence after 1-h exposure to histamine.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon could have serious physiological implications because it was observed not only in genetically manipulated systems, but also with endogenously expressed receptors. (16).…”
mentioning
confidence: 99%
“…There are potential phosphorylation sites in the third intracellular loop and in the carboxy-terminal tail of the H 2 receptor. The H 2 receptor mutant that lacks most of serine / threonine residues in the C-terminus can still be affected by GRK2 and GRK3, suggesting that the C-terminus is not involved in the GRK mediated desensitization of the histamine H 2 receptor (21,22). Further study is needed to clarify the receptor region responsible for the GRKmediated desensitization.…”
Section: Roles Of C-terminal Tails Of Histamine Receptorsmentioning
confidence: 99%
“…When co-expressed with H 2 receptor in COS-7 cells, G-protein-coupled receptor kinases (GRKs) 2 and 3 (also called βARK 1 and 2, respectively) augment the desensitization of the signaling characterized by decreased production of cAMP, whereas GRK5 and GRK6 do not affect the signaling (21). The desensitization process seems to involve the phosphorylation of the receptor (22). The region of the H 2 receptor interacting with these GRKs is not known so far.…”
Section: Roles Of C-terminal Tails Of Histamine Receptorsmentioning
confidence: 99%